Determinants of Currency Composition of Reserves : a Portfolio Theory Approach with an Application to RMB - Lu, Yinqiu (IMF Working Papers; Working Paper ;, 2019)
The way central banks manage their foreign reserve assets has evolved over the past decades. One major trend is managing reserves in two or more tranches-liquidity tranche and investment tranche-especially for those with adequate reserves. Incorporating reserve tranching, we have developed in this paper a central bank's reserve portfolio choice model to analyze the determinants of the currency composition of reserves. In particular, we adopt the classical mean-variance framework for the investment tranche and the asset-liability framework for the liquidity tranche. Building on these frameworks, the roles of currency compositions in imports invoicing and short-term external debt, and risk and returns of reserve currencies can be quantified by our structural model-a key contribution of our paper given the absence of structural models in the literature. Finally, we estimate the potential paths of the share of RMB in reserves under different scenarios to shed light on its status as an international currency.